Diversification of ortho-fused cycloocta-2,5-dien-1-one cores and 8 to 6-Ring conversion by sigma bond C-C cleavage - Eccleshare, Lee; Lozada-Rodriguez, Leticia; Cooper, Phillippa; Burroughs, Laurence; Ritchie, John; Lewis, William; Woodward, Simon (Wiley-VCH Verlag, 2016)
Sequential treatment of 2-C6H4Br(CHO) with LiC≡CR1 (R1 = SiMe3, tBu), nBuLi, CuBr∙SMe2 and HC≡CCHClR2 [R2 = Ph, 4-CF3Ph, 3-CNPh, 4-(MeO2C)Ph] at -50 oC leads to formation of an intermediate carbanion (Z)-1,2-C6H4{CA(=O)C≡CBR1}{CH=CH(CH–)R2} (4). Low temperatures (-50 oC) favour attack at CB leading to kinetic formation of 6,8-bicycles containing non-classical C-carbanion enolates (5). Higher temperatures ( 10 oC to ambient) and electron deficient R2 favour retro σ-bond C-C cleavage regenerating 4 which subsequently closes on CA providing 6,6-bicyclic alkoxides (6). Computational modelling (CBS-QB3) indicates both pathways are viable and of similar energies. Reaction of 6 with H+ affords 1,2-dihydronaphthalen-1-ols, or under dehydrating conditions, 2-aryl-1-alkynylnaphthlenes. Enolates 5 react in situ with: H2O, D2O, I2, allylbromide, S2Me2, CO2 and lead to the expected C-E derivatives (E = H, D, I, allyl, SMe, CO2H) in 49-64% yield directly from intermediate 5. The parents (E = H; R1 = SiMe3, tBu; R2 = Ph) are versatile starting materials for NaBH4 and Grignard C=O additions, desilylation (when R1 = SiMe) and oxime formation. The latter allows formation of 6,9-bicyclics via Beckmann rearrangement. The 6,8-ring iodides are suitable Suzuki precursors for Pd-catalysed C-C coupling (81-87%); while the carboxylic acids readily form amides under T3P® conditions (71-95%).